Employee Performance in Improving Population Administration Services in the Population and Civil Registration Office of East Halmahera Regency - Yuliana Dawanaka; Welly Waworundeng; Antonius Purwanto (Journal La Bisecoman, 2022)
This research aims to analyze how employee performance improves Population Administration Services at the Population and Civil Registration Service of East Halmahera Regency. This research uses Robbins' theory with indicators of performance quality, performance quantity, timeliness, effectiveness, independence. This research used a qualitative descriptive method with 9 informants consisting of the head of the department, head of the population identity section, staff of the identity section, head of the service and community cooperation section. The results of this research show that the performance of employees in population administration services at the population and civil registration services is not yet optimal, this can be seen from the fact that there are still several communities where the creation of population administration is still incomplete. Based on several things that need to be suggested to the population and civil registration service to further improve the quality of employee performance and it is hoped that they will further increase the timeliness in completing the preparation of population administration.